2006
DOI: 10.1111/j.1365-2621.2006.tb08913.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Injection, Packaging, and Storage Conditions on the Quality of Beef and Bison Steaks

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: : : : : The combined effects of injection, packaging (modified atmospher The combined effects of injection, packaging (modified atmospher The combined effects of injection, packaging (modified atmospher The combined effects of injection, packaging (modified atmospher The combined effects of injection, packaging (modified atmosphere packaging [MAP] with 70% O e packaging [MAP] with 70% O e packaging [MAP] with 70% O e packaging [MAP] with 70% O e packaging [MAP]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 32 publications
11
26
0
1
Order By: Relevance
“…Koch et al (1995) and Larick et al (1989) reported that bison were more tender, more juicy, and had lower shear force than beef cattle, even though a noticeable "off-flavour" was identified in bison. For shelf-life attributes, meat colour is one of the major concerns in bison, as bison meat is darker (Koch et al 1995) and discolours more rapidly (Dhanda et al 2002;Janz et al 2000;Pietrasik et al 2006) than beef. The exact mechanism for colour differences between beef and bison have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koch et al (1995) and Larick et al (1989) reported that bison were more tender, more juicy, and had lower shear force than beef cattle, even though a noticeable "off-flavour" was identified in bison. For shelf-life attributes, meat colour is one of the major concerns in bison, as bison meat is darker (Koch et al 1995) and discolours more rapidly (Dhanda et al 2002;Janz et al 2000;Pietrasik et al 2006) than beef. The exact mechanism for colour differences between beef and bison have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…), such as blast chilling, spray chilling, elevated temperature conditioning, moisture enhancement, and marination (Dhanda et al 2002;Janz and Aalhus 2006;Janz et al 2000Janz et al , 2001Pietrasik et al 2006) that have improved, in some cases, organoleptic characteristics of high-value cuts (i.e. ribeye), but have had limited or no significant effect on the development or stability of bison meat colour.…”
Section: Introductionmentioning
confidence: 99%
“…When available, bison can be sold fresh in steaks and burger patties at grocery stores. However, fresh bison meat discolors faster than beef (Janz et al, 2000;Dhanda et al, 2002;Pietrasik et al, 2006). This may be due to the higher pigment concentration and polyunsaturated fat content promoting oxidative instability in the meat .…”
Section: Introductionmentioning
confidence: 81%
“…It is highly likely the lower lipid oxidation in NIT packaging resulted from the oxygen impermeability of the film. Pietrasik et al (2006) observed that beef stored in vacuum packaging without embedded nitrite did not have a significant increase in TBARS over 3 wk of storage. While sensory characteristics were not measured here, the present result may also have implications for the eating quality of bison patties as higher levels of lipid oxidation in beef has been associated with higher perception of rancid flavors (Resconi et al, 2012).…”
Section: Effect Of Nit On Burger Patty Lipid Oxidationmentioning
confidence: 91%
“…Μερικοί ερευνητές ανέφεραν ότι η οξείδωση των πρωτεϊνών εξαιτίας του μαγειρέματος, εντοπιζόταν στις περιφέρειες των κυττάρων και, απέδωσαν αυτήν την οξείδωση, κυρίως στις πρωτεΐνες των μεμβρανών (Astruc et al 2007). Άλλοι ερευνητές βρήκαν ότι η θέρμανση ευνοούσε τη διαδικασία ζελατινοποίησης που προκαλείται από την οξείδωση των πρωτεϊνών (Parkington et al 2000), ενώ άλλοι διαπίστωσαν ότι οι χαμηλότερες θερμοκρασίες συντήρησης ευνοούσαν την οξειδοαναγωγική σταθερότητα της σιδηρομυοσφαιρίνης σε βόειο (Pietrasik et al 2006) και χοιρινό κρέας ).…”
Section: θερμοκρασία μαγειρέματος και συντήρησηςunclassified